2019
DOI: 10.1016/j.surfcoat.2019.124928
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite coatings based on graphene and siloxane polymers deposited by atmospheric pressure plasma. Application to corrosion protection of steel

Abstract: The present study proposes an alternative eco-friendly method to prepare a thin composite coating based on graphene embedded in siloxane polymers which can be used as application for the corrosion protection of steel. The nanocomposite coatings were elaborated by a dielectric barrier discharge using a nebulized colloidal suspension of graphene nanosheets (GNs) dispersed in hexamethyldisiloxane (HMDSO) used as the precursor for the polymer matrix. After obtaining a stable colloidal solution, it was nebulized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Then, electrochemical parameters are grouped in Table 1. From Table 1, it is clear that i corr values decreased sharply when the epoxy polymer DGPMDAP was added to the corrosive environment [43, 44]. Correspondingly, the inhibitory efficiency increases with increasing of DGPMDAP concentration and reaches a maximum value of 92% at 10 −3 M. The highest inhibitory efficiency of epoxy polymer DGPMDAP could be explicated due to higher molecular volume and the presence several heteroatoms that could be adsorb to metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…Then, electrochemical parameters are grouped in Table 1. From Table 1, it is clear that i corr values decreased sharply when the epoxy polymer DGPMDAP was added to the corrosive environment [43, 44]. Correspondingly, the inhibitory efficiency increases with increasing of DGPMDAP concentration and reaches a maximum value of 92% at 10 −3 M. The highest inhibitory efficiency of epoxy polymer DGPMDAP could be explicated due to higher molecular volume and the presence several heteroatoms that could be adsorb to metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…The adhesion and mutual bonding of polymer materials on metal surfaces is an important research direction in the field of surface science [ 14 , 15 , 16 ].At present, there are four main types of metal and non-metal adhesion mechanisms generally recognized in the world: mechanical interlocking theory, electronic theory, diffusion theory, and adsorption theory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This thin nanocomposite film can be considered as a process where the nanocomposite is directly prepared in situ via plasma on the metallic substrate. The results in the anti-corrosive properties proved to be excellent for the coated sample in relation to the target [122]. Ysiwata et al modified nanoparticles of hexagonal boron nitride using acrylic acid plasma to improve compatibility with an acrylic emulsion, and it was found that this treatment enhanced stability and viscosity and also got better corrosion resistance in an AISI 304 stainless steel [123].…”
Section: Treatment Of Nps Prior To Pncs Processingmentioning
confidence: 99%
“…Once the PNCs has been manufactured, in various applications are sought to have certain specific surface properties to improve its performance. For example, cleaning and conditioning the surface of the PNCs, enhancing the adhesion of coatings [124], generating antimicrobial properties [120,124,125], chemical resistance [122], catalytic activity [126], among others. In other cases, the objective is to expose NPs that became embedded in the polymer matrix during the manufacturing process by molecular fragmentation (impact ion process) on the PNCs [127].…”
Section: Plasma Treatment After Processing Of the Pncsmentioning
confidence: 99%